2010
DOI: 10.1002/eji.201040719
|View full text |Cite
|
Sign up to set email alerts
|

Molecular structure of the Mycobacterium tuberculosis virulence factor, mycolic acid, determines the elicited inflammatory pattern

Abstract: Mycolic acids (MAs) occur in the cell wall of Mycobacterium tuberculosis as variable mixtures of different classes and chain lengths. Here, we address the relationship between the structure and its inflammatory function of this virulence factor using single synthetic MA isomers, differing in oxygenation class and cis- versus α-methyl-trans proximal cyclopropane orientation. Analysis of bronchoalveolar inflammation, lung histopathology and alveolar macrophage transcription revealed a strong dependence on these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 59 publications
2
68
0
Order By: Relevance
“…The inhibition of the cyclopropanation of oxygenated MAs resulted in cell death of Mtb and increased susceptibility to antibiotics (Barkan et al, 2009). Synthetic cis-cyclopropyl MeO-MAs and keto-MAs were inflammatory, but a-methyl trans-cyclopropyl MeO-MAs showed reduced activity and a-methyl trans-cyclopropyl keto-MAs a-Methyl trans-cyclopropanes help mycolic acid folding were non-inflammatory (Vander Beken et al, 2011). In a recent study, pellicle growth of Mtb was shown to have an absolute requirement for keto-MAs (Sambandan et al, 2013).…”
Section: Villeneuve and Othersmentioning
confidence: 99%
“…The inhibition of the cyclopropanation of oxygenated MAs resulted in cell death of Mtb and increased susceptibility to antibiotics (Barkan et al, 2009). Synthetic cis-cyclopropyl MeO-MAs and keto-MAs were inflammatory, but a-methyl trans-cyclopropyl MeO-MAs showed reduced activity and a-methyl trans-cyclopropyl keto-MAs a-Methyl trans-cyclopropanes help mycolic acid folding were non-inflammatory (Vander Beken et al, 2011). In a recent study, pellicle growth of Mtb was shown to have an absolute requirement for keto-MAs (Sambandan et al, 2013).…”
Section: Villeneuve and Othersmentioning
confidence: 99%
“…Functional groups include cyclopropane, methoxy, keto, epoxy, diene and alkene moieties (Table S1). We first assessed GEM18-TCR activity to a panel of 12 synthetic MAs that all comprise the same short α-alkyl chains of C 23 or C 21 , but diverse meromycolate chains containing different functional groups at various locations, including the Mtb MAs JR1080, AD129, JRRR124, MH140, JR1046, and JRRR121 ( Fig. 3 and Table S1).…”
Section: Meromycolate Chain Functional Groups Dictate Gem-tcr Activitymentioning
confidence: 99%
“…Mycolates are a major lipid component of the Mtb cell wall and are key virulence factors (21). They comprise long chain β-hydroxy fatty acids, composed of a shorter unfunctionalised α-alkyl chain and a longer meromycolate chain that typically has two functional groups, providing the main source of structural diversity (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…They also produce inflammation (Vander Beken et al, 2011), and the most potent are methoxy-mycolates containing a cis-cyclopropane ring. Keto-mycolates with the same structural features were considered anti-inflammatory, whereas a-mycolates appeared inert (Vander Beken et al, 2011).…”
Section: Notably M Alvei Cr-21mentioning
confidence: 99%
“…They also produce inflammation (Vander Beken et al, 2011), and the most potent are methoxy-mycolates containing a cis-cyclopropane ring. Keto-mycolates with the same structural features were considered anti-inflammatory, whereas a-mycolates appeared inert (Vander Beken et al, 2011). However, our data clearly show that cord factor with only a-mycoloyl substituents (M. brumae) is able to induce variable amounts of all the cytokines under study; further, mmaA4 mutants of M. tuberculosis (in theory containing mostly di-cis-cyclopropanated a-mycoloyl substituents) induced high levels of TNF-a and IL-12p40 (Dao et al, 2008).…”
Section: Notably M Alvei Cr-21mentioning
confidence: 99%